Nonenzymatic Sensor Based on Glassy Carbon Electrode Modified by Platinum Nanoparticles Decorated Reduced Graphene Oxide for Glucose Detection in Human Urine - Nisa, Ulfiatun; Iswantini, Dyah; Ahmad, Shahrul Nizam; Mahat, Mohd Muzamir; Putra, Budi Riza; Saskito, Dinda Iryawati Bedy; Wahyuni, Wulan Tri (Jurnal Kimia Valensi, 2024)
This research aims to develop a sensitive and selective nonenzymatic electrochemical sensor for glucose detection using a glassy carbon electrode modified with platinum nanoparticles (PtNPs) decorated on reduced graphene oxide (RGO). The structural properties and surface morphology of PtNPs/RGO composite were characterized using Raman spectroscopy and scanning electron microscopy (SEM). In addition, cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques were employed to investigate glucose measurements in human urine samples. The developed sensor shows an increasing anodic peak of glucose with a linear response at a concentration range from 10 to 1000 µM, with a detection limit of 5 µM. The proposed sensor also demonstrated good reproducibility, indicated by the value of relative standard deviation (%RSD) of 3.9%, and maintained its current response over seven consecutive measurements. Moreover, the proposed sensor exhibited high selectivity for glucose detection against several potential interferences, such as potassium (K+), chloride (Cl−), magnesium (Mg2+), ascorbic acid, dopamine, and urea, with recovery values of 96-102%, which are acceptable within the analytical range. Furthermore, this proposed sensor successfully detected glucose in human urine samples, and their concentrations were not significantly different when measured with a commercial glucose sensor.